2015
DOI: 10.3390/ijerph120201928
|View full text |Cite|
|
Sign up to set email alerts
|

Using Nature-Based Rehabilitation to Restart a Stalled Process of Rehabilitation in Individuals with Stress-Related Mental Illness

Abstract: After a period of decrease, sick leave in Sweden due to psychiatric diagnoses is on the increase. The lack of established rehabilitation programmes for patients with stress-related mental disorders (SRMD) has opened up for the use of garden/nature in a multimodal rehabilitation context (Nature-Based Rehabilitation, NBR). Region Västra Götaland (VGR) started an NBR to offer additional rehabilitation for its employees on long-term sick leave due to SRMD, where initial care had not been sufficient. The aim was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 45 publications
1
49
0
Order By: Relevance
“…Choosing an ecovillage in the countryside as a setting for the intervention was therefore believed to be important. Based on our findings, we also proposed that there is evidence for the positive impact of a nature environment and horticultural or nature-based activity on mental health, which is in line with the findings of other studies [ 61 , 62 , 63 , 64 ]. Due to their poor mental health, some of the participants needed an even more sheltered environment to support their mental restoration such as a sheltered therapeutic garden.…”
Section: Discussionsupporting
confidence: 91%
“…Choosing an ecovillage in the countryside as a setting for the intervention was therefore believed to be important. Based on our findings, we also proposed that there is evidence for the positive impact of a nature environment and horticultural or nature-based activity on mental health, which is in line with the findings of other studies [ 61 , 62 , 63 , 64 ]. Due to their poor mental health, some of the participants needed an even more sheltered environment to support their mental restoration such as a sheltered therapeutic garden.…”
Section: Discussionsupporting
confidence: 91%
“…These findings support the premise that being in a forest environment may provide benefits when living with stress-related illness. Sahlin et al (2015) explored the effects of nature-based rehabilitation for people suffering from stress-related illness. Their results showed increased well-being scores and a reduction in healthcare consumption as well as reduced scores on burnout, depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…[87][88][89] Spending time in a garden or nature has been shown to be an effective therapy for stress-related mental health issues (i.e., nature-based rehabilitation). 90 In a blighted urban environment, the vacant-lot greening study mentioned above found decreased levels of self-reported high stress around newly greened vacant lots. 79 In addition, a small randomized trial found decreased ambulatory heart rate, as a dynamic measure of stress, among participants who walked in view of Bclean and greenedv acant lots compared to participants who walked in view of untreated vacant lots in their neighborhood.…”
Section: Urban Greening As Place-based Public Health Interventionmentioning
confidence: 97%